KEBIJAKAN HUKUM PIDANA DALAM PENANGGULANGAN KEJAHATAN ANAK - Jacob Hattu (Faculty of Law, Universitas Pattimura, 2014)
In particular the problem of crime committed by juveniles is usually referred to as delinquency and how efforts to overcome a complicated issue. This is because the crime or criminal offenses committed by the many factors that contribute and influence the behavior of the youth. Associated with criminal behavior committed by adolescents and a violation of legal norms and social. Thus, from the standpoint of criminal politics and global macro, then the non-penal efforts and strategic occupy key positions in tackling the causes and conditions that give rise to crime. Therefore tackling juvenile crime with criminal approach must be grounded.